Clay-containing polymer nanocomposites : from fundamentals to real applications - Ray, Suprakas Sinha, 1973- (Elsevier, 2013)
Clay-Containing Polymer Nanocomposites covers everything from fundamental understanding to real applications of clay-containing polymer nanocomposites, including environmental considerations. The book's coverage of fundamentals and generalities, in addition to in-depth coverage of polymer layered silicate nanocomposites, make it a valuable companion for beginners in the field as well as more seasoned researchers. This book provides a rare coherent approach to this class of materials. This title is ideal for polymer and material scientists, researchers, and engineers, including under- and post-graduate students who are interested in this exciting field of research. This book will also help industrial researchers and R & D managers who want to bring advanced polymeric material based products into the market. Details crystallization behavior and kinetics to aid in applications such as injection molding Covers melt-state rheological properties, aiding understanding of the processability of materialsPresents applications and market potential, supporting R & D managers who want to bring advanced polymeric material-based products into the market.